2020
DOI: 10.1029/2019ja027542
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Counterpart Signatures in Saturn's Auroras and ENA Imagery During Large‐Scale Plasma Injection Events

Abstract: Saturn's morningside auroras consist mainly of rotating, transient emission patches, following periodic reconnection in the magnetotail. Simultaneous responses in global energetic neutral atom (ENA) emissions have been observed at similar local times, suggesting a link between the auroras and large‐scale injections of hot ions in the outer magnetosphere. In this study, we use Cassini's remote sensing instruments to observe multiple plasma injection signatures within coincident auroral and ENA imagery, captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 98 publications
(202 reference statements)
1
14
0
Order By: Relevance
“…Such tail reconnection, and the consequent transport of tenuous energized plasma results in enhanced field‐aligned coupling currents, poleward contractions of dawn‐brightened aurora and energetic particle precipitation. Hot plasma is accelerated inwards towards Saturn, forming a dipolarization front, and causing the plasma sheet to expand away from the equator planetward of the reconnection region (see also previous studies of plasma injection signatures at Saturn, for example by Mitchell et al., 2009; Kinrade et al., 2020). Bradley et al.…”
Section: Internal and External Drivers Of Magnetospheric Storms Durinmentioning
confidence: 89%
See 1 more Smart Citation
“…Such tail reconnection, and the consequent transport of tenuous energized plasma results in enhanced field‐aligned coupling currents, poleward contractions of dawn‐brightened aurora and energetic particle precipitation. Hot plasma is accelerated inwards towards Saturn, forming a dipolarization front, and causing the plasma sheet to expand away from the equator planetward of the reconnection region (see also previous studies of plasma injection signatures at Saturn, for example by Mitchell et al., 2009; Kinrade et al., 2020). Bradley et al.…”
Section: Internal and External Drivers Of Magnetospheric Storms Durinmentioning
confidence: 89%
“…planetward of the reconnection region (see also previous studies of plasma injection signatures at Saturn, for example by Mitchell et al, 2009;Kinrade et al, 2020). Bradley et al (2020) reported several instances during the F ring and proximal Revs when Cassini was inbound in the northern lobe region and became engulfed by such hot plasma (the term 'Rev' is an abbreviation of revolution, and refers to an orbit of Cassini around Saturn defined from one apoapsis to the next).…”
Section: Accepted Articlementioning
confidence: 91%
“…As discussed in some detail below, these systems give rise to intervals of thickening and thinning of the nightside plasma/current sheet during their rotational cycles, as well as to north-south oscillations Morooka et al, 2009;Provan et al, 2012), with plasmoids being released preferentially when rotation phases associated with current sheet thinning sweep across the tail (Bradley et al, 2018;Jackman et al, 2016). Correspondingly, PPO-modulated injections of hot plasma into the outer region occur on the nightside, followed by rotation around the planet via dawn, as observed remotely both in energetic neutral atom (ENA) images and auroral emissions at various (ultraviolet (UV), infrared, and radio) wavelengths Kinrade et al, 2020;Lamy et al, 2013;Mitchell et al, 2005Mitchell et al, , 2009. These injection events are also associated with few-hour enhancements in Saturn kilometric radiation (SKR), an electromagnetic emission usually peaking in the frequency range~100-400 kHz, generated by the cyclotron maser instability of accelerated auroral electrons (Lamy et al, 2011).…”
Section: Internally Generated Dynamics In Saturn's Magnetospherementioning
confidence: 95%
“…As discussed in some detail below, these systems give rise to intervals of thickening and thinning of the nightside plasma/current sheet during their rotational cycles, as well as to north‐south oscillations (Cowley & Provan, 2017; Cowley et al, 2017; Morooka et al, 2009; Provan et al, 2012), with plasmoids being released preferentially when rotation phases associated with current sheet thinning sweep across the tail (Bradley et al, 2018; Jackman et al, 2016). Correspondingly, PPO‐modulated injections of hot plasma into the outer region occur on the nightside, followed by rotation around the planet via dawn, as observed remotely both in energetic neutral atom (ENA) images and auroral emissions at various (ultraviolet (UV), infrared, and radio) wavelengths (Bader, Badman, Cowley et al, 2019; Kinrade et al, 2020; Lamy et al, 2013; Mitchell et al, 2005, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Discrete, rotating regions of enhanced ENA intensity are commonly observed, interpreted as signatures of large-scale plasma injection from the magnetotail (e.g., Mitchell et al, 2005;Mitchell, Krimigis, et al, 2009;Mitchell et al, 2015;Krimigis et al, 2007). Typically appearing around midnight-dawn local times near Titan's orbit, the hot ion population (revealed through ENA detection) drifts around the planet with ∼ 60 − 70 % of the planetary corotation speed (Carbary, Mitchell, Brandt, Roelof, & Krimigis, 2008b;Carbary & Mitchell, 2014;Kinrade et al, 2020), eventually dispersing through charge exchange. These injection signatures sometimes persist for several planetary rotations (Paranicas et al, 2005), spreading with gradient-curvature drift (e.g., Mitchell, Krimigis, et al, 2009) and often leading to a partial ring or spiral morphology (e.g., Brandt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%